Rapid phenotypic evolution in multidrug-resistant Klebsiella pneumoniae hospital outbreak strains. Issue 4 (2nd April 2019) - van Dorp, Lucy; Wang, Qi; Shaw, Liam P.; Acman, Mislav; Brynildsrud, Ola B.; Eldholm, Vegard; Wang, Ruobing; Gao, Hua; Yin, Yuyao; Chen, Hongbin; Ding, Chuling; Farrer, Rhys A.; et al.
Abstract : Carbapenem-resistant Klebsiella pneumoniae (CRKP) increasingly cause high-mortality outbreaks in hospital settings globally. Following a patient fatality at a hospital in Beijing due to a bla KPC-2 -positive CRKP infection, close monitoring was put in place over the course of 14 months to characterize all bla KPC-2 -positive CRKP in circulation in the hospital. Whole genome sequences were generated for 100 isolates from bla KPC-2 -positive isolates from infected patients, carriers and the hospital environment. Phylogenetic analyses identified a closely related cluster of 82 sequence type 11 (ST11) isolates circulating in the hospital for at least a year prior to admission of the index patient. The majority of inferred transmissions for these isolates involved patients in intensive care units. Whilst the 82 ST11 isolates collected during the surveillance effort all had closely related chromosomes, we observed extensive diversity in their antimicrobial resistance (AMR) phenotypes. We were able to reconstruct the major genomic changes underpinning this variation in AMR profiles, including multiple gains and losses of entire plasmids and recombination events between plasmids, including transposition of bla KPC-2 . We also identified specific cases where variation in plasmid copy number correlated with the level of phenotypic resistance to drugs, suggesting that the number of resistance elements carried by a strain may play a role in determining the level of AMR. Our findings highlight the epidemiological value of whole genome sequencing for investigating multi-drug-resistant hospital infections and illustrate that standard typing schemes cannot capture the extraordinarily fast genome evolution of CRKP isolates.